Association of left atrial volume index with outcomes after transcatheter mitral valve repair for secondary mitral regurgitation: results from the EuroSMR registry. (14th October 2021) - Iliadis, C; Kalbacher, D; Lurz, P; Petrescu, A; Orban, M; Karam, N; Lubos, E; Thiele, H; Von Bardeleben, S; Hausleiter, J; Pfister, R; ,
Abstract: Background: The benefit of transcatheter edge-to-edge mitral valve repair (TMVr) in heart failure patients with secondary mitral regurgitation (SMR) shows large heterogeneity. A potential explanation might be the burden and chronicity of left-ventricular backward failure which is reflected by left atrial (LA) size. Purpose: To investigate the role of LA volume index (LAVi) in real-world SMR patients undergoing TMVr. Methods: SMR patients in a European multicenter registry were evaluated. Outcomes were evaluated according to LAVi at baseline. Main analysis was performed for all-cause mortality; residual mitral regurgitation, improvement of NYHA class and heart failure hospitalization were analyzed for patients available. Results: 823 included patients were divided according to LAVi into quintiles (≤42, 43–52, 53–62, 63–78, ≥79). A higher hazard for mortality occurred in the four upper quintiles compared to the lower quintile (HR [95% CI] 1.61 [1.08–2.4], 1.65 [1.11–2.46], 1.52 [1.02–2.26] and 1.35 [0.89–2.05]). The incidence of all-cause mortality per 100 patient-years was 14.6, 23, 23.9, 21.7 and 19.5, respectively. Consequently, a cut-off of 42ml/m 2 was adopted, which was associated with a significantly higher hazard for mortality after a mean of 589 days (HR 1.54 [95%-CI 1.1–2.1], p=0.01). Technical success rate (postprocedural MR ≤2+) was higher in large LAVi group (95% vs. 91%, p=0.045). The endpoints of heart failure hospitalization, improvement of NYHA class were not different among groups. Multivariable Cox regression analysis including age, EF<30%, diabetes mellitus and NTproBNP showed LAVi >42ml/m 2 to be an independent predictor of mortality. Conclusion: LA dilatation defined by LAVi>42 ml/m 2 was associated with higher mortality hazard in SMR patients undergoing TMVr after multivariable adjustment. Our findings warrant further study on whether timely TMVr intervention in patients with SMR and small LAVi can modify outcome. FUNDunding Acknowledgement: Type of funding sources: None.